2018
DOI: 10.3389/fcimb.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Comparison Among Global Isolates of L. interrogans Serovars Copenhageni and Icterohaemorrhagiae Identified Natural Genetic Variation Caused by an Indel

Abstract: Leptospirosis is a worldwide zoonosis, responsible for more than 1 million cases and 60,000 deaths every year. Among the 13 pathogenic species of the genus Leptospira, serovars belonging to L. interrogans serogroup Icterohaemorrhagiae are considered to be the most virulent strains, and responsible for majority of the reported severe cases. Serovars Copenhageni and Icterohaemorrhagiae are major representatives of this serogroup and despite their public health relevance, little is known regarding the genetic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Interestingly, the IZSLER database revealed that Leptospira ST17 occurs in different hosts (mouse, cat, hedgehog, horse, goat and cow), which indicates its ability to cause infection in a wide range of animal species. The sequencing of the lic12008 gene, which was recently reported by Santos et al [ 54 ] as useful in discriminating Icterohaemorrhagiae and Copenhageni serovars, allowed us to determine that the major portion (94%) of samples typed as ST17 represented serovar Icterohaemorrhagiae, and only a small portion (6%) represented serovar Copenhageni. The reliability of this molecular test for serovar discrimination is still unclear, and further studies are necessary, given that the serovar determinations of two isolates, as assessed by mAbs and by lic12008 sequencing, were not in agreement ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the IZSLER database revealed that Leptospira ST17 occurs in different hosts (mouse, cat, hedgehog, horse, goat and cow), which indicates its ability to cause infection in a wide range of animal species. The sequencing of the lic12008 gene, which was recently reported by Santos et al [ 54 ] as useful in discriminating Icterohaemorrhagiae and Copenhageni serovars, allowed us to determine that the major portion (94%) of samples typed as ST17 represented serovar Icterohaemorrhagiae, and only a small portion (6%) represented serovar Copenhageni. The reliability of this molecular test for serovar discrimination is still unclear, and further studies are necessary, given that the serovar determinations of two isolates, as assessed by mAbs and by lic12008 sequencing, were not in agreement ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A tract of the lic12008 gene of samples genotyped as ST17 (characterized as L. interrogans serogroup Icterohaemorrhagiae) was sequenced. The tract was recently found to be involved in the genetic distinction between serovars Icterohaemorrhagiae and Copenhageni [ 54 ], which are indistinguishable by MLST and MLVA. The analysis determines the presence of a single base insertion of a thymine nucleotide within a poly-thymine tract (9-bp long) in the lic12008 of all L. interrogans serovar Icterohaemorrhagiae isolates but not in Copenhageni strains.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the 16S RNA gene has been vastly supported as a good phylogenetic marker for Leptospira spp. classification (Fouts et al, 2016;Santos et al, 2018;Vincent et al, 2019) guarantees that this gene contains regions enabling the differentiation between the major groups of the Letospira spp. Moreover, using all sequences available at the GenBank database ensured that the design of the primers and probes in the current study had a broad and selective spectrum for the detection of all infectious Leptospira spp., with the exclusion of all saprophytic group and the novel clade of environmental Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic serovars of L. interrogans serovar Icterohaemorrhagiae (strain WFA135), an isolate from Rattus norvegicus in Tokyo, Japan, serovar Manilae (strain UP-MMC-NIID) 31,32 and a saprophytic L. biflexa serovar Patoc (strain Patoc I) were used in this study. The serovar of WFA135 was determined by multiple loci variable number of tandem repeats analysis (MLVA) and DNA sequencing of the lic12008 gene 32,33 . Bacteria were cultured in enriched Ellinghausen-McCullough-Johnson-Harris (EMJH) liquid medium (BD Difco, NJ, USA) containing 25 μg/mL spectinomycin at 30 °C for 2 ( L. biflexa ) or 4 ( L. interrogans ) days until the stationary phase.…”
Section: Methodsmentioning
confidence: 99%